2007
DOI: 10.1016/j.soilbio.2006.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Increase in soil pH due to Ca-rich organic matter application causes suppression of the clubroot disease of crucifers

Abstract: Clubroot disease of cruciferous plants caused by the soil-borne pathogen Plasmodiophora brassicae is difficult to control because the pathogen survives for a long time in soil as resting spores. Disease-suppressive and conducive soils were found during the long-term experiment on the impact of organic matter application to arable fields and have been studied to clarify the biotic and abiotic factors involved in the disease suppression. The fact that a large amount of organic matter, 400 t ha−1 yr−1 farmyard ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 31 publications
2
28
0
1
Order By: Relevance
“…The application of food factory sludge compost (FSC) to soil increased soil pH, calcium, carbon, nitrogen and phosphorus levels, and there could be additional effects of these elements on disease suppression. However, this is unlikely because of the fact that the suppressive effect in FSC‐treated soils was cancelled out by acidification with sulphuric acid (Niwa et al ., 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of food factory sludge compost (FSC) to soil increased soil pH, calcium, carbon, nitrogen and phosphorus levels, and there could be additional effects of these elements on disease suppression. However, this is unlikely because of the fact that the suppressive effect in FSC‐treated soils was cancelled out by acidification with sulphuric acid (Niwa et al ., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The objective of this study was to clarify the mechanism of disease suppression at neutral soil pH in the assessment of spore germination. The reliability and reproducibility of the germination assay system were examined in conjunction with the soil‐based plug‐pot bioassay (Niwa et al ., 2007), with particular emphasis on the validity of nuclear staining for the germination assay. It was uncertain, however, whether the assay system was sensitive enough to detect germination, because if spores germinated in response to root exudates (Macfarlane, 1970; Suzuki et al ., 1992), only a small proportion of spores in the vicinity of roots would germinate.…”
Section: Introductionmentioning
confidence: 99%
“…21) Neutralization of conducive soil by Ca(OH) 2 , CaCO 3 , and KOH suppressed clubroot disease of cruciferous plants caused by the soil-borne pathogen Plasmodiophora brassicae, and Ca compounds were more effective than KOH. 28) In this study, we studied variations in the physical and chemical properties of fresh and composted oyster shell samples. We also studied the efficacy of fresh and composted oyster shell meal as a lime fertilizer in comparison with commercial lime for soybean cultivation as a test crop.…”
mentioning
confidence: 99%
“…Niwa et al. () showed that calcium‐rich organic matter suppressed disease. This was due to the effect of increasing pH rather than the presence of calcium.…”
Section: Introductionmentioning
confidence: 99%